Implementasi Kelas Ibu Balita Sebagai Upaya Pencegahan Stunting - Trisna Yuni Handayani; Renny Adelia Tarigan; Andi Wilda Arianggara; Desi Pramita Sari; Nelli Roza (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
The incidence of short toddlers or stunting is one of the nutritional problems experienced by toddlers in the world today. Based on the results of the 2021 Indonesian Nutritional Status Survey (SSGI), the prevalence rate of stunting in Indonesia is 24.4%. One of the government's strategies in Peraturan Presiden Nomor 72 Tahun 2021 to reduce stunting rates is improving parenting. The purpose of this community service is to increase the knowledge of toddler mothers in realizing optimal toddler growth and development and preventing stunting events. The method used is the provision of education with lecture, discussion and simulation methods. The target of the activity is mothers who have toddlers aged 0–5 years. The counseling was carried out on March 29, 2022 at the Posyandu Kelurahan Tanjung Uma. The result of this community service is an increase in knowledge and understanding in toddler mothers about exclusive breastfeeding, increasing maternal knowledge in giving complementary foods and nutrition to toddlers and stunting, improving mothers' ability to monitor growth and carrying out developmental stimulation. The conclusion of this community service is that the toddler mother class can be applied as an effort to prevent stunting in toddlers.